Developing Students’ Nationalism Character through Video-Based Learning in Pancasila Education in the Disruption Era - Muhammad Hendri Nuryadi; Pipit Widiatmaka (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The digital era hurts the crisis of student character, especially the nationalism character. Some lecturers fail to respond wisely due to the low use of digital-based learning media. This study aims to analyze the role of Pancasila Education lecturers in fostering the character of nationalism in the era of disruption, and the strategy of the Pancasila Education course in developing the character of student nationalism through video-based learning in the era of disruption. This research uses a qualitative approach and descriptive research methods. Data collection techniques use interviews, observations, literature studies, and questionnaires. The data analysis used is interactive, while the research subjects are 2 lecturers and 28 students. The role of Pancasila Education lecturers is very important in fostering the character of student nationalism so that learning methods and media must be based on digital technology, especially video-based ones. Video-based learning for the Pancasila Education course is a useful strategy to develop the character of student nationalism because it is easily accessible. The results of this study are an alternative for lecturers and teachers in building the nationalistic character of students, considering that the digital era hurts the millennial generation.